Map of Alaska and the Klondike from a model by Cosmos Mindeleff / by W.H. Knight, based on the maps of the United States Coast and Geodetic Survey and other data - Knight, W. H. (Alaska Relief Map Co., 1898)
Shows trails, waterways, forts, warehouses, and missions.; Relief shown by shading and spot heights. Color 1:3,611,520